Humanisme dan nilai cinta lingkungan dalam cerita pendek karya Benny Arnas - Yulisetiani, Septi; Rohmatun, Isnaini Nur (Universitas Pendidikan Indonesia, 2021)
Benny Arnas' short stories need to be studied to reveal knowledge about the representation of humanism and the value of environmental love. Currently, the symptoms of dhumanization and environmental damage are increasing, so it is necessary to strengthen humanism and the character of loving the environment. This strengthening can be done with the media of literary works, one of which is short stories. The research was conducted on the short stories by Benny Arnas which were published in the Sunday newspaper and documented on the live play page. Through the ecological sasatra approach in Benny Arnas' short stories, it can be seen that certain short stories present a form of the value of love for the environment which is shown through the act of preserving nature, beauty and cleanliness. The characters shown in the short stories have human values that are shown through their wisdom towards fellow humans and the natural environment.